Classroom Gems: Games, Ideas and Activities for Primary PE - Allen, William (New Dehli Pearson, 2014)
Description Games, Ideas and Activities for Primary PE engages with all six key areas of the National Curriculum and offers over 100 simple and adaptable games and activities that P.E teachers will find invaluable.? Step-by-step instructions are provided for each activity, including variations for different age groups and abilities, making physical education fun and engaging for primary children of all ages.?? No specialist knowledge of PE is necessary and many ideas can be used either as five minute lesson starters or as the basis for an entire lesson.
Include Illustrations
Keywords: Educational games